UTILITY OF NEUTROPHIL-TO-LYMPHOCYTE RATIO, PLATELETS-TO-LYMPHOCYTE RATIO AND CALL SCORE FOR PROGNOSIS ASSESSMENT IN COVID-19 PATIENTS - Asghar, Asma; Saqib, Usman; Aijaz, Saba; Bukhari, Karamat Hussain Shah; Hayat, Arshad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To validate if Neutrophil-to-Lymphocyte ratio (NLR), Platelet-to-Lymphocyte ratio (PLR) or CALL score (a novel scoring model) predict worse prognosis such as need for Intensive Care Unit (ICU) Admission and Mortality in COVID 19 patients.Study Design: Prospective observational cohort study.Place and Duration of Study: Combined Military Hospital Lahore, from Mar 2020 to May 2020.Methodology: Consecutive symptomatic patients with confirmed COVID-19 infection by RT-PCR were included. Patients’ age, gender, comorbids and labs data including complete blood counts and serum LDH was recorded. neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and CALL Score were calculated. Main outcomes were need for Intensive Care Unit Admission/ventilator support and mortality.Results: A total of 125 patients were admitted with the diagnosis of COVID-19 infection. There were 35 (28%) Intensive Care Unit admissions, 17 (13.6%) required mechanical ventilation and 17 (13.6%) patients were deceased. Regression Analysis was done. For Intensive Care Unit Admission/ventilator support significant predictors were neutrophil-to-lymphocyte ratio (p=0.03), age greater than 50 (p=0.02), moderate CALL score (p=0.02) and high CALL Score (p=0.004). For hospital deaths, significant predictors included neutrophil-tolymphocyte ratio (p=0.001) and age more than 50 years (p=0.01), CALL Score was not significant (p=0.3 & 0.9). Platelet-to-lymphocyte ratio (p=0.9 and 0.8) and Diabetes (p=0.1 & 0.6) were not significant.Conclusion: Neutrophil-to-lymphocyte ratio and age more than 50 years are significant predictors for need for Intensive Care Unit Admission or Ventilatory support and in-hospital mortality. High CALL Score is a significant predictor of Intensive Care Unit Admission or ventilator support but not for in hospital mortality.